Implementasi Etika Bisnis Islam dalam Transaksi Jual Beli pada Pedagang Pasar Tradisional di Desa Mainan Kecamatan Sembawa Kabupaten Banyuasin - Firdaus Rahmadi; Nuraida Nuraida; Anang Walian (CV. Ulil Albab Corp, 2023)
The efforts of traders at the Toy Village Traditional Market in providing services to buyers must be carried out properly, apply business ethics and establish friendship. The research entitled